Пориста теплоізоляція на основі глинозему - Шумська, Любов Петрівна (НТУ "ХПІ", 2017)
Запропоновано детальний опис способу отримання пористого теплоізоляційного матеріалу на основі глинозему методом низькотемпературної поризації легкоплавкої сировини при мінімальних енергетичних затратах. У роботі досліджені основні теплофізичні процеси, що протікають в сировинній суміші при її нагріванні і спучуванні, завдяки чому можна прогнозувати основні структурні показники готового теплоізоляційного матеріалу, а також передбачити його теплофізичні властивості. Новий пористий теплоізоляційний матеріал можна використовувати для теплового захисту поверхонь у широкому діапазоні температур і вологості.

The article describes a detailed method for the production of a porous insulating material based on alumina by the method of low-temperature porosity of low-melting light-weight raw materials at minimum energy intensity. With the help of differential thermal analysis, the modes of heat treatment have been studied; the rational parameters of thermal bloating have been defined that allows implementing the process with minimal energy consumption with predicted thermal properties of obtained materials. The result of the study is the establishment of the temperature boundaries of the physicochemical processes in the raw mixtures during heating and the relationship between the composition of the mixture, the heating temperature, and the structure of the material. New porous insulating material can be used for thermal protection of surfaces in a wide range of temperatures and humidity.
The porous thermal insulation based on alumina
Keywords: теплоізоляційні пористі вироби; термічне спучування; вологовміст; тепломасообмін; теплопровідність; енерговитрати; thermal bloating; water contetnt; thermal conductivity; moisture content